DEVELOPING POP-UP BOOK MEDIA IN EARLY READING AT LOW CLASS - Suci Oktaviana (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2021)
This research was motivated by the lack of media in early reading at the low class. Pop-up book was a media that provided a more attractive visualization for students. Pop-up books provoked students' enthusiasm in reading and stimulated students' imagination. This type of research was development (R&D), using the ADDIE model consisting of 5 stages, namely analysis, design, development, implementation, evaluation . The data were obtained from the questionnaire filled in by validators and field experts viewed from 5 aspects, namely simplicity, emphasis, balance, integration, and media design. Then, the feasibility test by media experts obtained a percentage of 89.55% (very feasible), by material experts was 88.55% (very feasible), and by field experts on media design was 86.25% (very feasible), and on the material was 85.4% (very feasible). Overall, pop-up book media for early reading was very feasible.